PENGARUH PROGRAM PERSENJATAAN ULANGRUSIA TERHADAP BERHENTINYA KERJASAMA NUNN-LUGAR COOPERATIVE THREAT REDUCTION ANTARA AMERIKA SERIKAT DENGAN RUSIA - Bhismaya, I Gede Yudha; Dharmiasih, D.A. Wiwik; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   Cooperative Threat Reduction was the most successful cooperation between the Russia and the U.S., it was dubbed as cooperation that redefined the two countries relations post-cold war. Despite the reputation, the cooperation came to an abrupt end in 2013. This research views Russian Rearmament Program known as New Look as the catalyst for CTR’s termination thus attempts to see how the two events are connected. Qualitative-Explorative is chosen as the research methodology, and every materials are procured through variety of documents, and literature sources both online and printed. To explain how New Look affected Russian refusal to prolong CTR, the acquired data and materials are analyzed using Rational Choice Theory, the concept of National Security, and Balance of Threat. The research points that New Look drove rationalization by redefining aspects of Russia’s security, and the rationalization led to Russia’s decision to discontinue the long and successful cooperation with the U.S.   Key Words: Threat, national security, rational, cooperation